USO DEL LASER DENTAL - Sueldo, Efraín (1999)
Atecent commercial advertisement describes a" revolutionay" ... "Breakthrough in periodotal surgery that regenerates new attachment" Through the application of" a patented Laser ENAP procedure. "Despite FDA approval fO! sulcu1ar debridement, the use for 1aser fer ENAP and gingival curettage as proposed in the available evidence.